Spraying with encapsulated nitric oxide donor reduces weight loss and oxidative damage in papaya fruit - da Veiga, Julia C. (2024)
The combination of nitric oxide (NO) donors with nanomaterials has emerged as a promising approach to reduce postharvest losses. The encapsulation of NO donors provides protection from rapid degradation and controlled release, enhancing the NO effectiveness in postharvest treatments. Moreover, the application method can also influence postharvest responses. In this study, two application methods were evaluated, spraying and immersion, using S-nitrosoglutathione (GSNO, a NO donor) in free and encapsulated forms on papaya fruit. Our hypothesis was that GSNO encapsulated in chitosan nanoparticles would outperform the free form in delaying fruit senescence. In addition, this study marks the pioneering characterization of chitosan nanoparticles containing GSNO within the framework of a postharvest investigation. Overall, our findings indicate that applying encapsulated GSNO (GSNO-NP-S) through spraying preserves the quality of papaya fruit during storage. This method not only minimizes weight loss, ethylene production, and softening, but also stimulates antioxidant responses, thereby mitigating oxidative damage. Consequently, it stands out as the promising technique for delaying papaya fruit senescence. This innovative approach holds the potential to enhance postharvest practices and advance sustainable agriculture.